Before I let go - Nijkamp, Marieke (Sourcebooks Fire, 2018)
When Corey moves away from Lost Creek, Alaska, she makes her friend Kyra promise to stay strong during the long, dark winter, and wait for her return. Just days before Corey is to return home to visit, Kyra dies. The entire Lost community speaks in hushed tones, saying her death was meant to be. And they push Corey away like she's a stranger. With every hour, Corey's suspicion grows. Lost is keeping secrets--but piecing together the truth about what happened to her best friend may prove as difficult as lighting the sky in an Alaskan winter.